GLP-1 Receptor Agonists in Recreational Athletes: Emerging Weight-Reduction Strategy or Potential Health Risk? A Review of Current Evidence - Topolski, Kamil; Tłoczek, Wiktoria; Śliwa, Wiktoria; Twardowska, Daria; Jelonek, Barbara; Tomczak, Barbara; Porada, Dagmara; Wandasiewicz, Monika; Klubikowska, Karolina; Wandzel, Małgorzata (Quality in Sport, 2026)
Background: Glucagon-like peptide-1 receptor agonists (GLP-1 RAs) are effective pharmacological agents for obesity treatment and are increasingly used beyond clinical indications. Their growing popularity among recreational athletes seeking rapid fat loss raises concerns regarding potential effects on muscle mass, exercise capacity, and overall health. Aim: This review summarizes current evidence on the metabolic, musculoskeletal, and performance-related effects of GLP-1 receptor agonists in recreationally active individuals. Material and Methods: A narrative review of PubMed-indexed studies published between 2015 and 2026 was conducted. Randomized controlled trials, meta-analyses, and experimental studies evaluating GLP-1 RAs in relation to body composition, skeletal muscle outcomes, metabolic adaptation, exercise tolerance, and safety were included. English-language full-text articles were analyzed. Results: GLP-1 receptor agonists consistently induce significant weight reduction, primarily through fat mass loss, although decreases in lean body mass are also reported. Improvements in insulin sensitivity and cardiometabolic markers may support exercise tolerance. However, concerns include potential muscle mass reduction, inadequate energy availability, gastrointestinal adverse effects, and limited data on strength, recovery, and long-term performance adaptation in recreational athletes. Conclusions: GLP-1 receptor agonists are effective for weight reduction, but their use in recreational sport requires caution. Potential metabolic benefits should be balanced against risks related to muscle preservation and exercise capacity. Sport-specific longitudinal studies are needed to clarify safety and performance implications.